Evaluasi Perubahan Kadar Asam Kojat dalam Krim Pencerah Wajah pada Variasi Suhu dan Waktu Penyimpanan Menggunakan Spektrofotometri Visibel - Rafika Nur Hidayani; Dedi Hanwar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Kojic acid is one of the active ingredients commonly used in skin-lightening creams. This compound tends to be unstable at high temperatures, which can reduce its effectiveness. Indonesia’s tropical climate and high average temperatures exacerbate the risk of quality degradation. This study aims to analyze the effects of varying storage temperatures (4°C, 25°C, and 30°C) and storage time (Days 0, 3, 7, 14, and 28) on the decrease in kojic acid content in facial brightening creams, as well as to validate the visible spectrophotometric analysis method using FeCl₃ reagent based on linearity, accuracy, and precision parameters. Based on the validation parameters, the coefficient of determination (r²) for linearity was 0,9986, % recovery was 98,62%, and total %RSD was 3,91%. The results of the concentration determination tests showed a decrease in kojic acid levels during 28 days of storage under all temperature conditions (4°C, 25°C, 30°C). There was a significant difference in kojic acid levels among storage temperatures (Kruskal-Wallis, p = 0.003). The Dunn-Bonferroni test showed that 4°C differed significantly from 25°C and 30°C (p < 0.05), but not between 25°C and 30°C (p > 0.05). The Friedman test also showed a significant effect of time on the concentration at all three temperatures (p < 0.05). Thus, it is concluded that the higher the storage temperature and the longer the storage time, the greater the decrease in kojic acid content in the cream. These findings indicate that storage conditions can affect the quality of the active ingredient during product use by consumers; therefore, storage at a low temperature (4°C) is recommended to help maintain kojic acid levels in the cream formulation. Furthermore, the analytical method used met validation criteria, ensuring that the results obtained are scientifically reliable.